2018
DOI: 10.2967/jnumed.117.197186
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Biodistribution and Dosimetry of the Dopamine Transporter Radioligand 18F-FE-PE2I in Human Subjects

Abstract: F-()--(3-iodoprop-2-enyl)-2β-carbofluoroethoxy-3β-(4'-methyl-phenyl) nortropane (F-FE-PE2I) was recently developed and has shown adequate affinity and high selectivity for the dopamine transporter (DAT). Previous studies have shown promising results for F-FE-PE2I as a suitable radioligand for DAT imaging. In this study, we investigated the whole-body biodistribution and dosimetry ofF-FE-PE2I in healthy volunteers to support its utility as a suitable PET imaging agent for the DAT. Five healthy volunteers were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 21 publications
0
22
1
Order By: Relevance
“…The dosimetry of [ 18 F]FE-PE2I has been estimated in nonhuman primates and human subjects [146,147]. The estimated effective dose (ED) is 0.023 mSv/MBq, which is similar to that of other 18 F-labeled radioligands for brain imaging [148].…”
Section: New Tracers For Dopaminergic Imaging In Parkinsonian Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dosimetry of [ 18 F]FE-PE2I has been estimated in nonhuman primates and human subjects [146,147]. The estimated effective dose (ED) is 0.023 mSv/MBq, which is similar to that of other 18 F-labeled radioligands for brain imaging [148].…”
Section: New Tracers For Dopaminergic Imaging In Parkinsonian Syndromesmentioning
confidence: 99%
“…For the tracers described in this guideline, effective dose and absorbed dose (per MBq) to the highest exposed organs has been compiled from the available literature and is given in Table 4 [40,147,155,[163][164][165][166][167][168][169]. In most cases, following this guideline will lead to effective doses below 5 mSv per examination.…”
Section: Radiation Safetymentioning
confidence: 99%
“…[ 18 F]FE-PE2I, developed in 2009 [ 1 , 2 ], has, through several validity studies, proven to be a valuable positron emission tomography (PET) radioligand for dopamine transporter (DAT) imaging [ 1 8 ]. A clinical PET study with [ 18 F]FE-PE2I in twenty patients with early-stage PD showed an in vivo striato-nigral gradient of DAT loss [ 9 ], in agreement with post-mortem studies in patients and animal model studies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 F]FE-PE2I, developed in 2009 [1,2], has, through several validity studies, proven to be a valuable positron emission tomography (PET) radioligand for dopamine transporter (DAT) imaging [1][2][3][4][5][6][7][8]. A clinical PET study with [ 18 F]FE-PE2I in 20 patients with early-stage PD showed an in vivo striato-nigral gradient of DATloss [9], in agreement with post-mortem studies in patients, and animal model studies [10,11].…”
Section: Introductionmentioning
confidence: 54%